1977
DOI: 10.1111/j.1432-1033.1977.tb11400.x
|View full text |Cite
|
Sign up to set email alerts
|

The Immunochemistry of Peptidoglycan

Abstract: An albumin-peptide conjugate was synthesized, which carries pentaglycine peptides with Cterminal glycine residues as found in the interpeptide bridges of the peptidoglycan of many staphylococci. Immunization of rabbits with this synthetic immunogen yielded antisera containing predominantly antibodies against the peptide moiety of the conjugate. The quantitative precipitin and the Ouchterlony agar gel reaction with several synthetic protein-peptide-conjugates, immunoaffinity chromatography of the antisera on Se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

1978
1978
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…Hybridization analyses show that the 13-lactamase determinants from S. aureus and S. simulans are homologous, and it seems likely that the lysostaphin plasmid will show other similarities to the S. aureus 13-lactamase plasmids. Lysostaphin itself may be related to autolytic enzymes, which appear to be widely distributed in staphylococci (45). Although little is known about their properties, these enzymes are apparently associated with the cell wall of the producing organism and may play an essential role in reshaping the wall during cell growth and division.…”
Section: Discussionmentioning
confidence: 99%
“…Hybridization analyses show that the 13-lactamase determinants from S. aureus and S. simulans are homologous, and it seems likely that the lysostaphin plasmid will show other similarities to the S. aureus 13-lactamase plasmids. Lysostaphin itself may be related to autolytic enzymes, which appear to be widely distributed in staphylococci (45). Although little is known about their properties, these enzymes are apparently associated with the cell wall of the producing organism and may play an essential role in reshaping the wall during cell growth and division.…”
Section: Discussionmentioning
confidence: 99%
“…The glycan backbone and the peptide subunit attached to muramic acid are believed to be essentially identical in all staphylococcal strains. Some variation occurs in the interpeptide bridge with L-alanine or L-serine present in this structure, in addition to glycine, in some species of staphylococci (23).…”
Section: Discussionmentioning
confidence: 99%
“…The interpeptide bridge shows some species variation, and small structural differences have been detected immunologically in the interpeptide bridge of certain staphylococcal species. For example, Seidl and Schleifer (23) have demonstrated that antibodies raised in rabbits against a synthetic protein-peptide conjugate carrying pentaglycine peptides with free carboxyl groups can differentiate staphylococcal peptidoglycans without Cterminal glycine residues. Karakawa et al (11) have recently found evidence for strain-specific immunological difference in sonically treated S. aureus peptidoglycan preparations.…”
Section: Discussionmentioning
confidence: 99%
“…The humoral immune response to bacterial PG is complex, with at least five well-defined antigenic de terminants expressed by the molecule [11], namely: (1) the glycan strand [12]; (2) the N-terminal moiety of the non-cross-linked interpeptide bridge [13]; (3) C-terminal sequences of the interpeptide bridge [14]; (4) the non-cross-linked tetrapeptide of the peptide subunits, with C-terminal L-lysyl-D-alanine as the immunodominant group [15], and (5) the non cross-linked pentapeptide of the peptide subunits, with C-terminal D-alanyl-D-alanine as the immuno dominant group [16].…”
Section: Discussionmentioning
confidence: 99%